Labelisasi Produk Pangan UMKM di Kecamatan Pulung Ponorogo: Perspektif Sosiologi Hukum Islam - Icca Febriyanti; Abid Rohmanu (Jurnal Antologi Hukum, 2021)
This research departs from labelling MSME food products that do not contain an expiration date, production code, and inclusion of a halal label without halal certification from MUI carried out by business actors in Pulung, Ponorogo. Based on this, this study aims to explain the sociological review of Islamic law on the practice of labelling MSME products in Pulung, Ponorogo, and a review of the sociology of Islamic law on the factors behind the labelling practice of MSME products carried out by business actors in Pulung Ponorogo District. The research method used is qualitative with data collection techniques through interviews and documentation. From this study, it can be concluded that the labelling practice carried out by business actors follows the three basic ideas of the symbolic interactionism theory proposed by Herbert Mead. This result is because every action taken by business actors is translated from the human mind (mind) about oneself (self) and carried out in the community (society) where the individual is located. The factors behind business actors doing labelling follow the three basic premises of the symbolic interactionism theory proposed by Blumer. Meanwhile, in the application of sharia economic principles, the actions of business actors are not following the principles of honesty and truth; some business actors are dishonest in providing information on labels.